Fungal pathogens associated with mikania micrantha and their potential as biological control agent - Abd Kadir, Nurul Syuhaida (2016)
Mikania micrantha is an invasive weed that is spreading rapidly to many parts of the world including tropical countries. The abundance of M. micrantha in Malaysia is at present a severe problem for plantation area and idle land. This study were conducted to investigate and identify the fungal pathogens associated with M. micrantha and their potential as biological control agent. Cultural and chemical control are used extensively to control this invasive weed but it become less effective with buildup of weed resistance on herbicide and labor intensive. Introduction of biological agent will become an alternative method as well as reduce the environmental pollution. In this study, the sample materials were collected based upon disease symptoms shown on the plant parts around UPM Serdang. Isolation and purification of fungi were done in laboratory and followed by identification of fungi based on their morphological characteristics. Pathogenicity test on detached leaf done with focus on the effect of different fungal pathogen and different leaf stages of M. micrantha was done. Disease assessments were done to examine the pathogenic level of the isolated fungi based on disease incidence and disease severity. From disease severity data, Curvularia sp. is very pathogenic to M. micrantha as indicated by high AUDPC value (258.07 unit, P<0.05) and faster disease progress rate (0.26 unit/day, P<0.05). The time taken to reach 50% of disease severity is faster (8 days) compared to Colletotrichum sp. (>10 day). Pathogenicity of pathogen on different leaf stages showed older leaf stage is more susceptible to both fungal pathogens. From this study, spot, lesion and necrotic symptoms were exhibited and observed on the leaf parts as a result of pathogenic affect from the isolated fungi and their ability to inhibit the growth of M. micrantha by the development of disease.